Pathology of HIV seropositive: Forensic autopsy study in a tertiary care hospital, Bangkok, Thailand - Vichan Peonim (2018)
Objective: To retrospectively study the pathology of HIV seropositive in forensic autopsies. Material and Method: Three hundred thirty fi ve HIV seropositive cases, selected from 7,387 forensic postmortem inquests by law, were studied in Ramathibodi hospital between 2000 and 2010. The study topics were sex, age, cause of death, manner of death, and pathological features. Autopsies were done in 67 cases. The pathological features were classifi ed into fi ve groups, (a) HIV disease with infectious and parasitic diseases, (b) HIV disease with malignant neoplasms, (c) HIV disease with other specifi ed diseases, (d) HIV disease with other conditions, and (e) HIV disease with unspecifi ed pathology. Results: The average prevalence of HIV seropositive cases was 4.5%. The peak was 10.0% in 2001 and gradually decreased until 1.8% in 2010. The ratio of male:female was 4:1. The most manner of death was natural death (83.6%). In unnatural death cases, the most frequently method was suicide by hanging. The prevalence of HIV group (a) to group (e) were 56.7%, 6.0%, 3.0%, 17.9%, and 16.4%, respectively. Pulmonary tuberculosis is the most common found in group (a) with frequency of 28.4%. Kaposi's sarcoma of skin, coronary atherosclerosis, and fatty change of liver were frequently observed in HIV group (b) to group (d), respectively. The pathology showed multiple pathological features in each group, i.e., group (a) pulmonary tuberculosis, pneumonia, disseminated fungal infection, brain abscess, and meningitis, group (b) Kaposi's sarcoma of skin and acute lymphoblastic leukemia, group (c) coronary atherosclerosis, chronic pyelonephritis, gastritis, and cirrhosis of the liver, and group (d) cardiomegaly, fatty change of liver, pulmonary edema, and splenomegaly. Conclusion: HIV disease causes pathology of various organs. The severities vary from severe to asymptomatic disease. Five pathological patterns of HIV were established in this study that showed interesting topics, i.e., pulmonary tuberculosis was the most frequent and occurred (28.4%) in HIV disease with infectious and parasitic diseases while Kaposi's sarcoma of skin frequently occurred in HIV disease with malignant neoplasms. The decreasing rate of HIV transmitted infection in forensic postmortem may refl ect the success of using antiretroviral drug treatment in the National AIDS program during the ten -year period of this study.